2011
DOI: 10.1007/s11064-011-0462-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Vivo l-Acetylcarnitine Administration on ATP-ases Enzyme Systems of Synaptic Plasma Membranes from Rat Cerebral Cortex

Abstract: The maximum rates (V (max)) of some enzymatic activities related to energy consumption (ATP-ases) were evaluated in two types of synaptic plasma membranes (SPM) isolated from cerebral cortex of rats subjected to in vivo treatment with L: -acetylcarnitine at two different doses (30 and 60 mg kg(-1) i.p., 28 days, 5 days/week). The following enzyme activities were evaluated: acetylcholinesterase (AChE); Na(+), K(+), Mg(2+)-ATP-ase; ouabain insensitive Mg(2+)-ATP-ase; Na(+), K(+)-ATP-ase; direct Mg(2+)-ATP-ase; C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Our findings have revealed that the escape latency increases while the number of crossing platform and time spent in target quadrant is decreased by B(a)P as compared to control groups, indicating that the spatial memory is impaired in the rats exposed to B(a)P. These results are in agreement with Bouayed [26] who has reported that B(a)P exposure induces the impairments in the behavioral function of neonatal rats. Our data also reflects that the neurotoxic effects of B(a)P are restricted to 0.2 mg/kg and 2 mg/kg of B(a)P. Adenosine triphosphatase, a protease on the biofilm, exists in the histiocyte and organelle membranes and plays an important role in the substance transportation, energy conversion and information transmission [27]. Calcium adenosine triphosphatase and calcium-magnesium Data is presented in terms of the mean ± standard error of mean (M±SEM).…”
Section: Atpase Activitysupporting
confidence: 68%
“…Our findings have revealed that the escape latency increases while the number of crossing platform and time spent in target quadrant is decreased by B(a)P as compared to control groups, indicating that the spatial memory is impaired in the rats exposed to B(a)P. These results are in agreement with Bouayed [26] who has reported that B(a)P exposure induces the impairments in the behavioral function of neonatal rats. Our data also reflects that the neurotoxic effects of B(a)P are restricted to 0.2 mg/kg and 2 mg/kg of B(a)P. Adenosine triphosphatase, a protease on the biofilm, exists in the histiocyte and organelle membranes and plays an important role in the substance transportation, energy conversion and information transmission [27]. Calcium adenosine triphosphatase and calcium-magnesium Data is presented in terms of the mean ± standard error of mean (M±SEM).…”
Section: Atpase Activitysupporting
confidence: 68%
“…It is necessary to understand the true mechanisms of the regulation, maintenance and recovery of brain functions. It should be noted that studies on synaptic fraction levels were carried out along these lines from the beginning [4,18,[21][22][23][24][25][26][27][28][29][30][31].…”
Section: Natural Markers Of the Neuronal Systemsmentioning
confidence: 99%
“…However, since Ca 2+ (L)-ATP-ase is considered a ''capacitative'' component in Ca 2+ extrusion mechanism (K m for Ca 2+ of 82.6 lM, Villa et al, 2011), the modulation of presynaptic homoeostasis, transmembrane potential and cellular [Ca 2+ ] regulation is similar .…”
Section: Bioenergetics Of Frontal Cerebral Cortex Hippocampus Striamentioning
confidence: 99%
“…on nonsynaptic mitochondria located in the perikaryon of neurons, especially because the Gibbs free energy (DG°0) of these mitochondria is directly related to protein synthesis (Villa et al, 1989b), and on intra-synaptic mitochondria, located in vivo in synapses, whose DG°0 is mainly related to ions homoeostasis and neurotransmission (Benzi et al, 1993(Benzi et al, , 1994Gorini et al, 2002;Villa et al, 2002;Gilmer et al, 2010;Villa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%